POSITIVISASI NILAI SYARIAH DALAM REGULASI JAMINAN PRODUK HALAL DI INDONESIA (IAIN Tulungagung, 2022)
This article conducted in a research to legalize sharia values into nationally legal positivism or as a nationwide formal regulation. This research purposed to analyze the halal’s guarantee from a product into conclusion for how far the sharia values internalized into nationwide regulation. First, the implementation of Islamic law practice into nationwide regulation law must pass through the legal procedure. Secondly, the assurance of halal’s product guarantees aims to ensure that Muslim consumers are obtaining security and legal certainty over the consumption of circulating products and for producers to feel a positive impact by increasing business value added both in the production, distribution and marketing of halal food. Thirdly, regulation of halal products is an attemp to put sharia value into formal regulation by requiring halal product certification in all business forms.